My Precious Life: Strategi Membabat Narasi Mitos Pulung Gantung sebagai Rekonstruksi Perilaku Sosial Kelompok Rentan Bersama PKK Dusun Ngampel Gunungkidul: indonesia - Asfia, Nur; Putra, Dimas Brian Adi; Gunawan, Alvin Nuru Syah; Hidayat, Raka Pramudita; Paramesti, Mahia Nasywa; Kushartati, Sri (UII, 2025)
Data from the Yogyakarta Regional Police indicate that Gunungkidul Regency has the highest suicide rate in Yogyakarta. In Gunungkidul, nearly 20 cases happen every year. The cases of suicide in Gunungkidul are usually linked with the myth of